2023
DOI: 10.2991/978-2-38476-086-2_107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mid-semester Assessment in Cultivating Critical Thinking of Elementary School Students

Melly Rahmawati,
Yulia Maftuhah Hidayati

Abstract: Critical thinking skills can provide the right direction for thinking, working and assisting students in determining the proper steps in solving problems. The elementary school level plays a vital role in developing these thinking skills. A student's ability to think critically can be measured by providing an indicator of High Older Thinking Skills (HOTS). Mid-semester Assessment (PTS) is a series of assessment components that elementary school students must pass after the middle of the semester. This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For data analysis using SPSS version 23 software, this data analysis makes it possible to test hypotheses and make conclusions based on empirical evidence. The operational definition of the social media marketing activities variable consists of entertainment, interaction, trendiness, and customization (Khajeh Nobar et al, 2020); (Seo & Park, 2018); the operational definition of the brand experience variable consists of product interaction, customer service, brand presence, and consistency (Amer et al, 2023); (Rahmawati & Hidayati, 2023); the operational definition of the brand trust variable consists of product quality, transparency, social responsibility, and security and privacy (Roets et al, 2014); (Chung & Kim, 2014); the operational definition of brand equity variables consists of perceived quality, brand awareness, brand association, and brand loyalty (Rahmawati & Hidayati, 2023); (Amer et al, 2023). The results of the experiment's reliability shown in Table 2 above prove that all indicators have a Cronbach alpha value for each instrument > 0.60, so it can be concluded that all the instruments used are reliable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For data analysis using SPSS version 23 software, this data analysis makes it possible to test hypotheses and make conclusions based on empirical evidence. The operational definition of the social media marketing activities variable consists of entertainment, interaction, trendiness, and customization (Khajeh Nobar et al, 2020); (Seo & Park, 2018); the operational definition of the brand experience variable consists of product interaction, customer service, brand presence, and consistency (Amer et al, 2023); (Rahmawati & Hidayati, 2023); the operational definition of the brand trust variable consists of product quality, transparency, social responsibility, and security and privacy (Roets et al, 2014); (Chung & Kim, 2014); the operational definition of brand equity variables consists of perceived quality, brand awareness, brand association, and brand loyalty (Rahmawati & Hidayati, 2023); (Amer et al, 2023). The results of the experiment's reliability shown in Table 2 above prove that all indicators have a Cronbach alpha value for each instrument > 0.60, so it can be concluded that all the instruments used are reliable.…”
Section: Methodsmentioning
confidence: 99%
“…Copyright © 2024, SULTANIST: Jurnal Manajemen dan Keuangan Sekolah Tinggi Ilmu Ekonomi Sultan Agung products (H. J. Kim, 2012); (Huaman-Ramirez & Merunka, 2019). Generation Z has unique characteristics and consumption preferences that are different from previous generations, so it is necessary to understand how brand experiences can be tailored to their preferences and expectations (Yu & Yuan, 2019); (Rahmawati & Hidayati, 2023). This research can explore various aspects of brand experience that influence brand equity in fashion products, such as product quality, customer service, interaction with the brand via social media, and physical or online store experience.…”
mentioning
confidence: 99%